A cold model study of mass transfer in Q-BOP - Prasad N.; Singh S.; Malhotra S.L. (My University, 2025)
At steel-making temperature, chemical kinetics can rarely be the rate-limiting step. Thus most of the reactions are limited by the rate of mass transfer to and from the reaction interface. The overall rate of mass transfer may be controlled by gas phase mass transfer or liquid phase mass transfer. Since in Q-BOP, the rate of reaction may be controlled by the rate of mass transfer in gas phase or in liquid phase, both were studied in a cold model. The different variables studied were tuyere diameter, jet direction, flow rate of gas and tuyere depth. The results of gas phase mass transfer indicate that the effect of tuyere diameter and jet direction is very small. For Reynolds number less than 9000 the effect of flow rate and tuyere depth is given by the equation, K g A/L 0 Q = 0·02 d 0 + 0·043, whereas for Reynolds number greater than 9000 the effect of flow rate and tuyere depth is given by the equation, K g A/L 0 Q=0·061 d 0+0·046. Similarly the liquid phase mass transfer coefficient is independent of the tuyere diameter and the shrouding gas, and is not much affected by the jet direction. The effect of gas flow rate and tuyere depth is given by the equation, K L A=0·077 (Q)0·75(L 0)0·61. © 1989 Indian Academy of Sciences.